Are There Other Muscle Fibers on the Orbicularis Oris Muscle in the Upper Lip?. Issue 6 (27th September 2022) - Park, Jung-Ah; Rho, Nark Kyung; Lee, Hye-In; Yeo, In-Seung; Koh, Ki-Seok; Song, Wu-Chul
Abstract : Background: The elevator muscles of the upper lip are the levator labii superioris alaeque nasi, levator labii superioris, and zygomaticus minor muscles, which function by means of their insertions into the skin of the upper lip. However, many textbooks and journal articles state that no muscle fibers are present on the orbicularis oris muscle in the upper lip. The authors attempted to determine whether there is a superficial muscle layer in addition to the orbicularis oris muscle in the upper lip. Methods: The authors performed gross dissections of 10 formalin-fixed cadavers and applied micro–computed tomography to six formalin-fixed cadavers. The fine dissection of the upper lip was performed in a layer-by-layer manner that elucidated its muscle layers. The entire layer of the upper lip was separated and pretreated with phosphotungstic acid for micro–computed tomography. The samples used for micro–computed tomography were repurposed for use in histologic analysis. An ultrasonography study was also performed. Results: The presence of a muscle layer on the orbicularis oris muscle was confirmed in all samples. The elevator muscle fibers of the upper lip formed a layer by combining with connective tissue. Micro–computed tomography indicated lower terminal insertions of the elevator muscles throughout the upper lip. All parts of the upper lip skin were inserted into the orbicularis oris muscle. The histologic findings were similar to those of micro–computed tomography. Conclusion: The authors' findings could be used to improve aesthetic and surgical procedures performed on the upper lip, such as correction of gummy smile and transverse upper labial crease, or postresection reconstruction of the upper lip.